Puszkin i Owidiusz - Schade, Gerson (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2019)
Alexander Pushkin knew what he shared with Ovid. Both were exiled, having enjoyed a splendid life, both were highly gifted, and not too shy of erotic adventures – of which they speak amply in their poetry. The Russian formalist Tynyanov pointed at such similarities, inventing the literary genre of ‘docufiction’.